A procedure to calibrate and perform the bender element test (2012)
The bender element test method is used in the laboratory to obtain the shear wave velocity of soils. Despite its apparent simplicity, there is still no standard for this test. A number of factors affects the reliability of the results. These factors are taken into account to design and build a BE system in a triaxial cell. A method to calibrate the system is proposed, using aluminum rods of different lengths. Recommendations are made regarding to the selection of the frequency of the pulse used to produce the perturbation for the test execution. Finally, a series of tests carried out on two kinds of sand specimens are presented.